Chromosomal evolutionary dynamics of four multigene families in Coreidae and Pentatomidae (Heteroptera) true bugs - Bardella, Vanessa Bellini [UNESP]; Fernandes, José Antônio Marin; Cabral-de-Mello, Diogo Cavalcanti [UNESP] (Springer Nature, 2016)
Previous chromosome mapping of multigene families in Pentatomomorpha (Heteroptera) insects, which was restricted to the major rDNA, revealed remarkable conservation of number of clusters and chromosomal positions. Aiming to understand the chromosomal organization and evolutionary patterns of multigene families in karyotypes of Heteroptera, we performed a chromosomal mapping using four distinct multigene families in representatives of Coreidae (ten species) and Pentatomidae (five species). A single pair of the major rDNA cluster (18S rDNA probe) and a single pair of the minor rDNA cluster (5S rDNA probe), both terminally located were primarily observed, being, in most species, located in distinct chromosomes. However, some alternative patterns were also observed. In species in which the U2 snDNA and H4 gene clusters were mapped, they were mainly located in one autosomal pair each, wherein the H4 gene cluster was located in different positions. Our data suggest that the karyotype diversity reported in Coreidae is not reflected in the distribution diversity of multigene families. This contrasts with the data for Pentatomidae, with a conserved gross karyotype but a discrete diversity in the location of the clusters of multigene families, indicating genome dynamics for these markers. The findings are discussed to shed light on the possible causes for the conservation or variation observed and to assist in understanding the chromosomal evolutionary trends in the group.
Keywords: Fluorescence in situ hybridization; H4 histone; rDNA; U2 snDNA